2020
DOI: 10.3390/ijms21114010
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Intrinsically Disordered Proteins in the Genus Camelus

Abstract: Intrinsically disordered proteins/regions (IDPs/IDRs) fail to fold completely into 3D structures, but have major roles in determining protein function. While natively disordered proteins/regions have been found to fulfill a wide variety of primary cellular roles, the functions of many disordered proteins in numerous species remain to be uncovered. Here, we perform the first large-scale study of IDPs/IDRs in the genus Camelus, one of the most important mammalians in Asia and North Africa, in order to explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Camels can fluctuate their body temperature from 34 ∘ C to 41.7 ∘ C and can conserve water by not sweating [ 2 ]. Additional members of the camelid family included in our study are the Bactrian camel ( Camelus bactrianus ) and the Wild Bactrian camel ( Camelus ferus ) of Asia, and the alpaca ( Vicugna pacos ) of South America [ 4 , 38 ]. The extreme variation among their natural habitats opens up a series of questions about how the environment influences TEs in camelids.…”
Section: Introductionmentioning
confidence: 99%
“…Camels can fluctuate their body temperature from 34 ∘ C to 41.7 ∘ C and can conserve water by not sweating [ 2 ]. Additional members of the camelid family included in our study are the Bactrian camel ( Camelus bactrianus ) and the Wild Bactrian camel ( Camelus ferus ) of Asia, and the alpaca ( Vicugna pacos ) of South America [ 4 , 38 ]. The extreme variation among their natural habitats opens up a series of questions about how the environment influences TEs in camelids.…”
Section: Introductionmentioning
confidence: 99%
“…upon PRC1 trimer formation, as recently demonstrated for other similar motifs (Alderson et al, 2023). Considering that about 34% of the human proteome codes for intrinsically disordered regions, with ∼47% of proteins containing long disordered regions (≥30 disordered residues, with an average length of 214 residues, (Alshehri et al, 2020)), our study shows how important it is to systematically characterize those regions computationally and experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…The function of a given protein is often determined by its 3D structure; however, comparative studies on structure-to-function mechanisms have led to the realization that some proteins lack stable 3D structures in whole or in part, yet still play critical functions in the cell. Such proteins/regions with no well-defined stable structure are known as intrinsically disordered proteins (IDPs) and intrinsically disordered regions (IDRs), and occur throughout eukaryotic proteomes [ 9 , 10 , 11 ]. Disordered segments of at least 30 consecutive residues in length are termed long disordered regions (LDRs), and have been previously used as markers to distinguish disordered proteins [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, conformational flexibility allows disordered proteins to interact with multiple partners using a larger interaction surface, which translates into greater versatility and speed of interaction. It has been shown that protein disorder is significantly involved in molecular recognition processes, intracellular signalling machinery, and post-translational modifications [ 11 , 13 ]; disordered proteins thus contribute to the regulation of various biological processes [ 14 , 15 ]. Furthermore, although IDPs/IDRs are widespread in eukaryotic proteomes, relative to the three domains of life (archaea, bacteria, and eukaryotes), viruses are characterized by the widest spread of disordered proteome content [ 16 ].…”
Section: Introductionmentioning
confidence: 99%